Laryngeal mask vs. laryngeal tube trial in pediatric patients (LaMaTuPe): a single-blinded, open-label, randomized controlled trial [data] - Katzenschlager, Stephan; Mohr, Stefan; Kaltschmidt, Nikolai; Peterstorfer, Franziska; Weilbacher, Frank; Günther, Patrick; Ries, Markus; Weigand, Markus A.; Popp, Erik (Universität, 2024)
Background Children have poor hypoxia tolerance; hence, airway management is crucial. While endotracheal intubation is the gold standard, this requires extensive experience. Current guidelines recommend the usage of laryngeal masks (LM) over laryngeal tubes (LT) based on randomized-controlled trials (RCT) using first-generation supraglottic airway (SGA) devices. This study assesses insertion time, first and overall pass success in children <18 years with the latest generation SGA. Methods This prospective, monocentric RCT included children <18 years old undergoing elective anesthesia. Patients were allocated in a 1:1 ratio to the LM (control) or LT (intervention) group. The primary endpoint was the insertion time, starting with removing the face mask until the first reliable etCO2 trace was observed on the ventilator. In failed attempts, a declaration of failure was used as the endpoint. Secondary outcomes included first- and overall pass success (FPS / OPS) rates. Subgroup analyses were performed on pre-defined age groups: 0-2, 3-6, 7-11, and 12-17 years. Due to the high cross-over rate, per-protocol and as-treated analyses were performed. Patients and caregivers were blinded to the group assignment. Findings The final intention-to-treat analysis included 135 patients, 74 allocated to the LM and 61 to the LT group. The median age was 4·9 and 5·4 years, respectively. Median insertion time was significantly longer in the LT group (37 seconds vs. 31 seconds; p = 0·031). In addition, the LT was associated with a lower odds ratio for FPS and OPS with 0·043 (95% confidence interval (CI) 0·015 to 0·129) and 0·012 (95% CI 0·001 to 0·100). Subgroup analyses found no differences in the insertion time, while there were significant differences in FPS and OPS in the three youngest age groups. LT was associated with a higher rate of complications. Interpretation This RCT demonstrates the LM's superiority over the LT, especially in younger children. (2024-01-23)
Gesehen am 16.09.2024
Keywords: Forschungsdaten; Datenbank